Advances in Analytical Techniques for Water Quality Assessment - Shashank Gupta (International Journal of Environmental Noise and Pollution Control, 2024)
Assessing the quality of water is essential for preserving ecological balance and public health. This study evaluates new developments in analytical methods that are meant to improve the accuracy, effectiveness, and reach of water quality monitoring. While fundamental, conventional procedures like spectrophotometry and chromatography have drawbacks in terms of sensitivity and real-time capability. By allowing quick and precise pollutant and contaminant identification, emerging technologies such as sensor networks, remote sensing, molecular diagnostics, nanotechnology, and artificial intelligence are transforming the study of water quality. Case studies include examples of real-world implementations, such as satellite-based evaluation of huge water bodies and continual monitoring in urban water systems. These advances promise to boost international efforts towards sustainable water resource management and preservation, despite obstacles related to cost, data management, and uniformity.
Keywords: Next Generation Sequencing; Sensor Technologies; Solid phase extraction; quality assessment